1992
DOI: 10.1007/bf00224154
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA sequence polymorphisms among wheat varieties

Abstract: A DNA marker detection strategy that allows the rapid, efficient resolution of high levels of polymorphism among closely related lines of common wheat (Triticum aestivum) has been developed to circumvent the apparent lack of restriction fragment length polymorphism in many important self-pollinated crop species. The technique of randomly amplified polymorphic DNA (RAPD) was combined with a denaturing gradient gel electrophoresis system (DGGE) to explore DNA sequence polymorphisms among different genotypes of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 24 publications
3
19
0
2
Order By: Relevance
“…This homogeneity of 73% is probably due to the fact that all the wheat genotypes used in Brazil have a common origin. Similar (though not as extreme) RAPD results were also obtained with British (Devos & Gale, 1992) or USA (He et al, 1992) varieties, but Sun et al (1998) also found extreme homogeneity (79% to 88%, using 32 arbitrary primers) among respectively Chinese winter and spring common wheat. He et al (1992) combined RAPD analysis with the DGGE (denaturing gradient gel electrophoresis) technique, and even with this potentially more discriminating combination obtained an overall similarity index of 62%.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…This homogeneity of 73% is probably due to the fact that all the wheat genotypes used in Brazil have a common origin. Similar (though not as extreme) RAPD results were also obtained with British (Devos & Gale, 1992) or USA (He et al, 1992) varieties, but Sun et al (1998) also found extreme homogeneity (79% to 88%, using 32 arbitrary primers) among respectively Chinese winter and spring common wheat. He et al (1992) combined RAPD analysis with the DGGE (denaturing gradient gel electrophoresis) technique, and even with this potentially more discriminating combination obtained an overall similarity index of 62%.…”
Section: Resultssupporting
confidence: 71%
“…Similar (though not as extreme) RAPD results were also obtained with British (Devos & Gale, 1992) or USA (He et al, 1992) varieties, but Sun et al (1998) also found extreme homogeneity (79% to 88%, using 32 arbitrary primers) among respectively Chinese winter and spring common wheat. He et al (1992) combined RAPD analysis with the DGGE (denaturing gradient gel electrophoresis) technique, and even with this potentially more discriminating combination obtained an overall similarity index of 62%. Quantitative estimates of genetic homogeneity based on RAPD markers were obtained by Lanza et al (1997) in maize (37%), Graham & McNicol (1995) in Rubus (61%), Williams & St. Clair (1993) in tomato (63%), and Colombo et al (1998) in Manihot (65%).…”
Section: Resultssupporting
confidence: 71%
“…These discrepant results from other studies in the area can be explained by the study methodology (RAPD). RAPD has not proven effective for detecting variability in wheat due to the complex genome (allohexaploid) of this cereal, according to results of Devos and Gale (1992) in England and He et al (1992) and Riede et al (1994) in the United States. Besides, the genotypes studies were mostly specifically adapted to environments of cold and rainy climate and acidic soils.…”
Section: Resultsmentioning
confidence: 99%
“…RAPD markers provide a useful alternative to RFLP analysis for screening markers linked to a single trait within near isogenic lines and bulked segregants. He et al (1992) reported the development of a DNA polymorphism detection method by combining RAPD with DGGE (denaturing gradient gel elecrophoresis) for pedegree analysis and fingerprinting of wheat cultivars. RAPD markers can be converted to more user-friendly Sequence Characterized Amplified Region (SCAR) markers, that display a less complex banding pattern.…”
Section: Marker Assisted Selection In Wheat Breedingmentioning
confidence: 99%